Blocking of Other Party's Account Used by Suspect of Money Laundering Crime in Narcotics Case - Sulistianor, Eko (Scholar Center, 2023)
This study aims to analyze the action of blocking accounts of other parties used by suspects of money laundering crimes in narcotics cases. The research adopts a normative legal approach with a descriptive nature. The focus of this study is on the process and legal implications of blocking accounts of other parties in narcotics cases involving money laundering. The legal approach in this research includes analyzing relevant laws and understanding related legal principles. The findings of this study will provide insights into the practice of blocking accounts in the context of narcotics law enforcement and money laundering, as well as its implications within the criminal justice system. The conclusion of this research will offer a better understanding of how the process of blocking accounts of other parties can contribute to the effective handling of narcotics and money laundering cases.